Length–weight relationships for Eutropiichthys murius (Hamilton, 1822), Coilia reynaldi Valenciennes, 1848 and Johnius gangeticus Talwar, 1991 from lower stretch of the River Ganga, India. (30th July 2018) - Karna, Subodha K.; Baitha, Raju; Ray, Archisman; Mondal, Amit; Swain, Himanshu S.; Chanu, Thangjam N.; Ramteke, Mitesh H.; Manna, Ranjan K.; Das, Basanta K.
Abstract: Length‐weight relationships (LWRs) for three fish species from the River Ganga (India) is presented. Sampling was conducted from the lower stretch of the River Ganga (Patna: 25°36′51.66″N & 85°12′7.02″E to Freserganj: 21°35′40.58″N & 88°15′28.92″E) during April, June and September and December of 2017. Specimens were caught using gill nets (18 nos.; mesh 18–32 mm), and bag nets (3 nos.; mesh 14–22 mm). The values a and b from LWRs ‐were found to be 0.007 and 2.977 for Eutropiichthys murius ; 0.003 and 3.001 for Coilia reynaldi ; 0.009 and 3.010 for Johnius gangeticus .